2014
DOI: 10.4141/cjps2013-193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative yield, disease resistance and response to fungicide for forty-five historic Canadian wheat cultivars

Abstract: Martens, G., Lamari, L., Grieger, A., Gulden, R. H. and McCallum, B. 2014. Comparative yield, disease resistance and response to fungicide for forty-five historic Canadian wheat cultivars. Can. J. Plant Sci. 94: 371–381. Forty-five historic Canadian spring wheat cultivars, ranging from Red Fife (1870) to modern cultivars, were compared for yield and disease resistance in field trials from 2007 to 2010. A split-plot design was used to test yield, leaf rust and Fusarium head blight resistance, with or without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Over 100 leaf rust (Lr) genes have been numerically designated (McIntosh et al, 2017), but many older Lr genes have reduced effectiveness (such as Lr13, and Lr16) due to evolving pathogen populations . When comparing historical and modern cultivars, Martens et al (2014) reported that modern cultivars had partial or complete resistance against leaf rust as compared with historical cultivars. When comparing historical and modern cultivars, Martens et al (2014) reported that modern cultivars had partial or complete resistance against leaf rust as compared with historical cultivars.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over 100 leaf rust (Lr) genes have been numerically designated (McIntosh et al, 2017), but many older Lr genes have reduced effectiveness (such as Lr13, and Lr16) due to evolving pathogen populations . When comparing historical and modern cultivars, Martens et al (2014) reported that modern cultivars had partial or complete resistance against leaf rust as compared with historical cultivars. When comparing historical and modern cultivars, Martens et al (2014) reported that modern cultivars had partial or complete resistance against leaf rust as compared with historical cultivars.…”
mentioning
confidence: 99%
“…These race-specific genes must be supplemented with durable, long-lasting resistance genes such as Lr34 and Lr46, as they confer slow-rusting resistance (Singh et al, 1998;Singh and Huerta-Espino, 2003). When comparing historical and modern cultivars, Martens et al (2014) reported that modern cultivars had partial or complete resistance against leaf rust as compared with historical cultivars. Lr34 has become an important source of resistance in Canadian germplasm due to its durability , which may be attributed to synergies amongst other resistance genes (German and Kolmer, 1992).…”
mentioning
confidence: 99%
“…The contrary case would also be possible when farmers value traits of an old variety and new varieties could be marketed with the name of the old one. As recently released wheat varieties are usually better than the old ones in many features including resistance to disease and yield performance [ 28 ], farmers’ misidentification is ‘ False-Negative ’ when recently released varieties are misidentified and reported with names of old varieties, e.g. a farmer reporting a given variety grown as Kakaba (released in 2010) when DNA FP identified it as Kubsa (released in 1994), and ‘ False-Positive ’ when actually old varieties are misidentified and reported with names of recently released varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Even when this manual method provides an accurate and precise quantification, it is time-consuming and entails the intrinsic intra- and inter-rater variability [ 19 ]. In the case of the symptoms caused by pathogens or chewing insects, the high contrast between damaged/undamaged regions facilitates the repeatability and reproducibility of the results using automatic programs such as Fiji [ 13 , 20 ] or APS Assess [ 21 , 22 ]. In contrast, cell content feeders (mites or thrips) and phloem feeders (aphids) produce subtle symptoms difficult to recognise by automatic software programs.…”
Section: Introductionmentioning
confidence: 99%